Non-Formal Legitimacy of Constitutional Change and Public Perception in The Reform of the 1945 Constitution Through Constitutional Court Decisions - Hasanah, Siti; Jiwantara, Firzhal Arzhi (Jurnal IUS Kajian Hukum dan Keadilan, 2025)
Problematics of the legitimacy of non-formal constitutional changes through judicial decisions in the context of constitutional reform in Indonesia, with a focus on public perception as the main determinant of acceptance or rejection of these changes. Constitutional changes that do not go through formal procedures, carried out through the interpretation of judicial institutions, raise debates about the limits of institutional authority and the integrity of basic norms in the legal system. The purpose of the study was to evaluate how public perception affects the legitimacy of non-formal constitutional change through constitutional court decisions. This research uses a juridical-normative approach with the support of qualitative data analysed descriptively and evaluatively on several Constitutional Court decisions that are considered to contain elements of changes in constitutional norms. The novelty of this research lies in emphasizing the analysis of the relationship between public perception, trust in judicial institutions, and the direction of constitutional reform. The results show that without public support, constitutional change through non-formal channels risks delegitimization, and has the potential to create a crisis of confidence in constitutional institutions. This research contributes to promoting transparency, participation and accountability in the practice of judicial-based constitutional reform.